Pengolahan Limbah Lumpur Minyak Bumi (Oil Sludge) Kegiatan Hulu Migas Di Bob PT. Bumi Siak Pusako – Pertamina Hulu Dengan Metode Biopile Dan Komposting - Darojat, Irfa; Herlica, Inne; Wulandari, Dewi; Yulianto, Andik (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2024)
Oil sludge waste is a potential pollutant for the environment and a major problem in upstream oil and gas activities. The high content of hydrocarbons in oil sludge has the potential to contaminate soil, water and groundwater. The remediation approaches, both physical and chemical, for oil sludge waste have been applied, but the costs are quite high and their effectiveness is inadequate. Two of the economical and environmentally friendly oil sludge waste processing technology options are biopile and composting. The aim of this research is to explore the application of biopiles and composting to reduce total petroleum hydrocarbon (TPH) levels. There are 4 variations in the biopile, namely B-0 (oil sludge, soil and bulking agent), B-1 (oil sludge, soil, bulking agent and inoculum) B-2 (oil sludge, soil, bulking agent, inoculum and green compost), and B-3 (oil sludge, soil, bulking agent, inoculum and chemical fertilizers), while in composting there are 3 variations namely C-0 (oil sludge, soil and bulking agent), C-1 (oil sludge, soil, bulking agent and green compost), C-2 (oil sludge, soil, bulking agent and chemical fertilizer) with an observation period of 55 days. Biopile application reduced TPH at B-0, B-1, B-2, and B-3 by 67%, 78%, 82%, and B-3 78% consecutively. Composting application reduced TPH at C-0 by 61%, at C-1 by 67%, and at C-2 by 62%. The results implies that the application of bioremediation is able to reduce TPH levels.